ANALISIS RISIKO PRODUKSI DAN FAKTOR FAKTOR YANG MEMPENGARUHI RISIKO PRODUKSI USAHATANI JAHE LAHAN GAMBUT DI KECEMATAN PONTIANAK UTARA - Febrian, Ryan; Kurniati, Dewi; Kusrini, Novira (Universitas Galuh, 2023)
The national economy benefits significantly from the horticulture sub-sector. Biopharmaceutical plants are plants in the horticulture sub-sector which have various advantages. Ginger is a plant that has long been used for biopharmaceuticals as an export product. However, there is no perfect or cheap framework for ginger development yet, which leads to low quality and efficiency. Even though North Pontianak Subdistrict is the largest ginger producing area in Pontianak City, there are several challenges, especially fluctuations in ginger production over several years. The purpose of this study was to analyze the level of production risk and the factors that influence the production of ginger farming on peatlands in North Pontianak sub-district. There were 35 people who became respondents to the study, and this research was a population study. The research was conducted by purposive sampling, and using a quantitative descriptive method. Analysis of the level of production risk is carried out by analyzing the coefficient of variation (CV) and the factors that influence production risk using the cobb function analysis of Douglass just and pope model. This research can be used as a consideration for reducing the production risk of ginger farming in North Pontianak District so as to provide benefits in agriculture. The results showed that the level of production risk in North Pontianak Subdistrict was low, and the factor affecting production was urea fertilizer and land area affecting production risk.